Silencing endogenous mutant P53 Using Sirna Induces P73-Mediated Apoptosis in Human Head And Neck Squamous Cell Carcinoma - Arief Ichwan, Solachuddin Jauhari; Taher, Muhammad; Masa-Aki, Ikeda (2011)

(untitled)
Loss of p53 tumor suppressor function is a common event in numerous types of human cancer including Head and Neck Squamous Cell Carcinoma (HNSCC). p73, a member of the p53 family gene has striking structural homology and similar interrelated functions with the p53 gene; transactivate p53 responsive genes, and induce cell cycle arrest or apoptosis. In contrast to p53, p73 is rarely mutated in human cancers. Therefore targeting the p73 pathway of apoptosis could be a candidate approach to treat human cancers. However,certain mutant p53 proteins expressed in HNSCC cells that encode arginine polymorphism at codon 72(72R) have been known to inactivate p73 through physical interaction. We have reported previously that the endogenous mutant p53 protein (p53R248Q) expressed in human HNSCC HSC-4 cells contained 72R polymorphism. Therefore, silencing expression of such endogenous mutant protein may restore the p73 function in suppressing HSC-4 cell growth. Here we show that treatment with small-interfering RNA(siRNA) specific to inhibit the expression of endogenous mutant p53R248Q protein induced apoptosis in HSC-4 cells. Moreover, the expression genes involved in p73-regulated growth arrest and apoptosis were also upregulated, indicating that the apoptotic activity is indeed due to restoration of p73 function. These results also suggest a potential use of siRNA specific for mutant p53 to treat HNSCC. Keywords: HNSCC, gene therapy